Functional organic fertilizers can alleviate tobacco (Nicotiana tabacum L.) continuous cropping obstacle via ameliorating soil physicochemical properties and bacterial community structure - Chen, Dan; Wang, Mei; Wang, Gang; Zhou, Yujie; Yang, Xiaoe; Li, Jiangzhou; Zhang, Cuiping; Dai, Kuai (Frontiers in Bioengineering and Biotechnology, 2022)
Continuous cropping obstacle (CCO) in tobacco is a prevalent and intractable issue and has not yet been effectively solved. Many researchers have favored exploring environmentally friendly and sustainable solutions to CCO (e.g, the application of (bio-) organic fertilizers). Therefore, to study the effects of functional organic fertilizers (FOFs) on tobacco CCO, we applied five types of fertilizers in a tobacco continuous cropping field with red soil (i.e., CF: tobacco-special chemical fertilizers; VOF: vermicompost-based FOF; HOF: humic acid-based FOF; WOF: wood biochar-based FOF; COF: compound FOF). The tobacco plant agronomic traits, leaf yield, economic value, and chemical quality (nicotine, total sugar, K2O, Cl contents, etc.) were evaluated via the continuous flow method. Meanwhile, we determined rhizosphere soil physicochemical properties, phenolic acids content, and bacterial community diversity by high-throughput sequencing. The results show that FOFs improved the tobacco plant agronomic traits, leaf yield (by 2.9–42.8%), value (by 1.2–47.4%), and chemical quality when compared with CF. More content of NH4+-N, available P, and available K were discovered in the rhizosphere soil in VOF, HOF, and WOF. The rhizosphere sinapic acid and total phenolic acids content declined in the FOF treatments (1.23–1.56 and 7.95–8.43 mg kg−1 dry soil, respectively) versus those in the CF treatment (2.01 and 10.10 mg kg−1 dry soil, respectively). Moreover, the rhizosphere bacterial community structure changed under FOF functions: the beneficial microbes Actinobacteria, Firmicutes, Streptomyces, and Bacillus increased, and the harmful microbes Acidobacteria and Gemmatimonadota decreased in abundance. There was a positive correlation between the tobacco leaf yield and soil NH4+-N, TC content, and the relative abundance of Proteobacteria and Actinobacteriota. In summary, the application of VOF and WOF is a modest, practical, and environmentally friendly strategy to alleviate tobacco CCO from the standpoint of recycling solid waste.